Consumption and Employment Effects of Income Redistribution in Pakistan (The Pakistan Development Review, 1984)
The argument that growth and equality are two opposite objectives and the conviction that if the former is preferred in the short run, the latter will automatically follow in the long run, though very popular in the past, have become somewhat controversial in recent years. Available evidence from the developing countries does not seem to support the 'trickle down' theory. It is being increasingly felt that the solution to the problem of poverty does not lie in mere maximization of the GNP. Economists have now started stressing the need for 'direct attack on poverty' (6, pp.42- 44] and for specific policies with growth implications for different groups in the Society (2, p. xiii] . Redistribution of income among different groups is therefore emerging as an important policy objective in many developing countries, including Pakistan.